Russian Federation : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2002)
The Selected Issues paper and Statistical Appendix analyzes output developments in the Russian Federation since the 1998 crisis. It outlines near-term growth prospects for the economy. The paper highlights that output growth accelerated in 1999 and the first half of 2000, but has slowed since then. The initial output recovery was led by import substitution as a result of the large exchange rate depreciation in 1998. One finding in the context of an overall policy package is that the real exchange rate and oil prices were the main determinants of growth after the 1998 crisis.